Horticultural plant use as a so‐far neglected pillar of ex situ conservation. Issue 5 (28th June 2021) - Ismail, Sascha A.; Pouteau, Robin; van Kleunen, Mark; Maurel, Noëlie; Kueffer, Christoph
Abstract: We demonstrate how native and nonnative plant taxa used as ornamentals in private and public urban green spaces can significantly strengthen plant conservation in time of extinctions by expanding the capacity for ex situ living collections and raising awareness among professional and private gardeners and plant collectors. Based on global databases, we document the current representation of threatened plant taxa in horticulture compared to collections in botanical gardens. A substantial number of threatened taxa are already used in gardening, however, there is great unused potential—especially to reach high enough representation of genetic diversity and plant material for reintroduction and restoration programs. Considering urban greening as an integral part of ex situ conservation strategies can provide critically needed additional space and human resources for ex situ collections, while increasing the often low genetic, species and phylogenetic diversity of many newly established plantings that make them vulnerable to climate change and disease risks.